SANZ ORO, R. (1999). "Los Departamentos de Orientación en Educación Secundaria: Roles y funciones". Barcelona: Cedecs. Psicopedagogía. 269 págs - Rufino Cano González (Universidad de La Rioja, 2013)
SANZ ORO, R. (1999). Los Departamentos de Orientación en Educación Secundaria: Roles y funciones. Barcelona: Cedecs. Psicopedagogía. 269 págs.